Respons Peserta Didik Terhadap E-Modul Praktikum IPA pada Materi Konduktor dan Isolator - Asri Widowati; Jumadi Jumadi; Fitria Lafifa; Mirsya Adelia (Postgraduate, University of Mataram, 2023)
This study is a quantitative study of calculating student responses to the development of e-modules science practicum on conductors and insulators. This study aims to determine the response of students to the e-module which is declared eligible for testing. Student responses were measured using a response questionnaire. Response Questionnaire used in the validity and reliability test before being used. The validity test was carried out on 4 instrument experts to measure precisely. Reliability tests were carried out to generate agreement values between validators. The product trial was conducted at the Darul Dakwah Integrated Junior High School, Sooko District, Mojokerto Regency in class VIII. The sampling technique was purposive sampling. Student responses to the science practicum e-module on conductors and insulators material were given to 16 students at Darul Dakwah Terpadu Junior High School, Sooko District, Mojokerto Regency and received a very good response with a score of 89%.Â